FINANCIAL ANALYSIS AS A TOOL FOR MAKING FINANCIAL DECISIONS IN THE SYSTEM OF INTERNATIONAL FINANCE - Skyba, Hanna; Kryshtal, Halyna; Myroniuk, Odarka; Lytovchenko, Ruslan; Khimich, Sviatoslav (Current Problems of Sustainable Development, 2026)
The article examines the role of financial analysis as an important tool for making financial decisions in the system of international finance. It is substantiated that under conditions of globalization, digital transformation of the economy, increased volatility of financial markets, geopolitical instability, inflationary processes, and growing competition in the international environment, financial analysis becomes one of the key components of effective financial management. The study emphasizes that financial analysis provides comprehensive information support for assessing the financial condition, liquidity, solvency, profitability, business activity, and investment attractiveness of enterprises and financial institutions operating in global markets. The paper analyzes modern approaches to financial analysis and highlights the main analytical methods and indicators used in the process of making strategic and operational financial decisions. Particular attention is paid to the assessment of financial risks, management of capital structure, forecasting of cash flows, evaluation of investment projects, and determination of business value in the context of international financial relations. The study proves that effective financial analysis contributes to minimizing risks and increasing the efficiency of investment, credit, and management decisions. Special emphasis is placed on the current trends in the digitalization of financial analysis. The article investigates the impact of artificial intelligence technologies, Big Data, predictive analytics, automated information systems, and modern digital platforms on the transformation of analytical processes in international finance. It is determined that the use of innovative technologies allows enterprises and financial institutions to improve the accuracy, efficiency, and reliability of analytical calculations, accelerate decision-making processes, and adapt more effectively to changes in the global financial environment. The research also identifies the main challenges facing financial analysis in the modern international financial system, including increasing uncertainty, fluctuations in exchange rates, regulatory changes, and the integration of ESG principles into financial management. It is concluded that the development of adaptive analytical models and the implementation of digital technologies are necessary prerequisites for improving the quality of financial decisions and ensuring sustainable economic development in the conditions of global instability.